2010
DOI: 10.1364/ao.49.001414
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse light propagation in biological media by a time-domain parabolic simplified spherical harmonics approximation with ray-divergence effects

Abstract: We present a simplified spherical harmonics approximation for the time-domain radiative transfer equation including the source-divergence effect. This leads to a set of coupled partial differential equations (PDEs) of the parabolic type that model diffuse light propagation in biological-tissue-like media. We introduce a finite element approach for solving these PDEs, thereby obtaining the time-dependent spatial profile of the fluence. We compare the results with the diffusion equation and Monte Carlo simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…However, CCD cameras have a limited dynamic range and read-out noise limits their ultimate sensitivity. The second design avoids the potential limitations of CCD camera detection by employing highly sensitive single-photon counting technology based on the use of such detectors as photomultiplier tubes or avalanche photodiodes [10][11][12][13] . The drawback of these more sensitive detection methods is that each detector can only collect light at a single point; therefore, to achieve dense tissue sampling, either many detectors have to be used (which is very expensive), or many projections have to be imaged with the same detector (which can be time consuming).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, CCD cameras have a limited dynamic range and read-out noise limits their ultimate sensitivity. The second design avoids the potential limitations of CCD camera detection by employing highly sensitive single-photon counting technology based on the use of such detectors as photomultiplier tubes or avalanche photodiodes [10][11][12][13] . The drawback of these more sensitive detection methods is that each detector can only collect light at a single point; therefore, to achieve dense tissue sampling, either many detectors have to be used (which is very expensive), or many projections have to be imaged with the same detector (which can be time consuming).…”
Section: Discussionmentioning
confidence: 99%
“…Carefully transfer the imaging bed and mouse back to the fluorescence tomography system. Choose the number of source positions to collect data about the mouse for each imaging slice (32), the integration time for each TPSF measurement (1 s), the number of iterations for each source position (10), and the position and number of desired imaging slices from the CT image stack from Step 3.6. The numbers in parentheses are typical values for each imaging parameter yielding ~ 5 minutes of data acquisition per imaging slice.…”
Section: Video Linkmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that low order SP N equations provide sufficiently accurate results for biomedical optics [16,6]. For simplicity, we hereby consider the lowest possible order N¼3 (N¼1 is shown to be the DE) to both obtain applicable results and lower the complexity of the calculations presented; calculations for higher orders are similar.…”
Section: The Sp N Modelmentioning
confidence: 99%
“…Parallel to this, a DOT algorithm that exploits TPSF data and incorporates constrained optimization methods has been is implemented [5]. As the forward model, the time-dependent parabolic simplified spherical harmonics equations (TD-pSP N ) are used [7]. In this work we extend the studies presented in [6] to three-dimensional media and full multi-view TPSF data collection, simulating our mentioned experimental system [5].…”
Section: Introductionmentioning
confidence: 99%